LEXICAL AND CONTEXTUAL MEANINGS OF ALIENATION IN RADIOHEAD’S OK COMPUTER SONGS - Sulistio Tri Widodo; Ismawati Ike Nugraeni; Zulia Chasanah (Universitas Duta Bangsa Surakarta, 2026)
This study investigates how lexical and contextual meanings construct the theme of alienation in three songs from Radiohead's album OK Computer, namely ok, No Surprises, and Karma Police. The primary objective is to examine the interaction between lexical and contextual meanings in constructing alienation, an area that remains underexplored in semantic studies of song lyrics. A descriptive qualitative approach is employed, analyzing nine representative linguistic units, three from each song, selected from the lyrics. The analysis is guided by Kroeger's framework of lexical meaning and Feist's framework of contextual significance. The findings reveal that alienation is encoded through semantic domains such as emptiness, injury, waste, authority, technology, and identity. At the lexical level, expressions like 'emptiest,' 'landfill,' and 'karma' carry stable denotative meanings. However, within the album's thematic context, these meanings transform into symbolic representations of psychological detachment, emotional exhaustion, alienated labor, social surveillance, technological dehumanization, and identity fragmentation. The study concludes that alienation emerges implicitly through the interaction between lexical choice and discourse context, demonstrating that meaning in song lyrics is dynamic and context-dependent. These findings highlight the importance of integrating lexical and contextual perspectives in semantic analysis of contemporary musical texts.